Optimisation of cooperative spectrum sensing with ultra-wideband signalling. (4th February 2015) - Bielefeld, Daniel; Fabeck, Gernot; Zivkovic, Milan; Mathar, Rudolf
Reliable detection of primary user activity by spectrum sensing is of fundamental importance for cognitive radio systems. The objective of cooperative spectrum sensing is to combine the detection results of multiple cognitive radios in order to maximise the probability of detecting unused spectrum while meeting a required reliability of detecting primary user activity. In this paper, an optimisation strategy for cooperative spectrum sensing is proposed consisting of two parts. The first part is a Kullback-Leibler distance-based optimisation approach for the local decision thresholds. For the transmission of the local decisions, which can be realised by ultra-wideband underlay communications, in the second part an application-specific power control strategy is presented. The feasibility and effectiveness of the concepts are validated by real spectrum sensing results. The employed practical setup is based on software defined radio and detects a WiMAX-like OFDM signal.